8.0k views
2 votes
F= ((-5,1),(2,2),(1,-2))g=((2,-5),(-4,-2),(1,1))Find (f+g)(1)

User Nworks
by
4.8k points

1 Answer

3 votes

To find (f+g)(1), we can start by rewriting it as:


(f+g)(1)=f(1)+g(1)

The function f and g have a set of pairs. We are looking for the pairs that have the first number "1", we want the second number. In both, they are the last pair.

For f this is (1,-2), so:


f(1)=-2

For g this is (1,1), so:


g(1)=1

So, substituting into the first expression, we have:


(f+g)(1)=f(1)+g(1)=-2+1=-1

User Hatfinch
by
5.2k points